2009
DOI: 10.1073/pnas.0813330106
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and age-dependent seizures in a mouse model of severe myoclonic epilepsy in infancy

Abstract: Heterozygous loss-of-function mutations in the ␣ subunit of the type I voltage-gated sodium channel NaV1.1 cause severe myoclonic epilepsy in infancy (SMEI), an infantile-onset epileptic encephalopathy characterized by normal development followed by treatment-refractory febrile and afebrile seizures and psychomotor decline. Mice with SMEI (mSMEI), created by heterozygous deletion of NaV1.1 channels, develop seizures and ataxia. Here we investigated the temperature and age dependence of seizures and interictal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
209
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(229 citation statements)
references
References 39 publications
(46 reference statements)
12
209
3
2
Order By: Relevance
“…4C). The pattern of epileptiform electrical activity preceding and during the seizures induced in F/+:Dlx-Cre + mice was similar to those characterized previously in global Na V 1.1 heterozygotes (14,15) …”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…4C). The pattern of epileptiform electrical activity preceding and during the seizures induced in F/+:Dlx-Cre + mice was similar to those characterized previously in global Na V 1.1 heterozygotes (14,15) …”
Section: Resultssupporting
confidence: 53%
“…These global heterozygous mice exhibit temperature-induced and spontaneous seizures, mild ataxia, and premature death (14)(15)(16). Na V 1.1 channels are expressed in both excitatory and inhibitory neurons (3,6), yet electrophysiological studies in dissociated hippocampal neurons from DS mice showed selective loss of sodium current and excitability in GABAergic interneurons (14,17).…”
mentioning
confidence: 99%
“…A first animal model of DS has been generated in mice through a targeted deletion of a major exon in the SCN1A gene [137]. Homozygous null Scn1a−/− mice developed ataxia and died around P15, whereas heterozygous Scn1a1/-mice had hyperthermic-induced seizures and spontaneous seizures [137].…”
Section: Models Of Dravet Syndromementioning
confidence: 99%
“…Homozygous null Scn1a−/− mice developed ataxia and died around P15, whereas heterozygous Scn1a1/-mice had hyperthermic-induced seizures and spontaneous seizures [137]. A second mouse model has been generated through knock-in of a stop codon into the SCN1A gene (R1407X, in exon 21) [138].…”
Section: Models Of Dravet Syndromementioning
confidence: 99%
See 1 more Smart Citation